Application of the Analytic Hierarchy Process (AHP) in Determining Bridge Maintenance in Sekadau Regency - Dwi Kartika Wati; Slamet Widodo; , Nurhayati (Jurnal Serambi Engineering, 2025)
A bridge is an infrastructure structure that connects two points separated by natural and artificial obstacles. The importance of bridge maintenance lies in prioritizing the safety and smooth operation of the community, reducing construction costs, and extending the life of bridge infrastructure. The problem is that there has been an increase in mobility in several public spaces after the pandemic, so adequate facilities and infrastructure are needed. However, adding bridge infrastructure is currently not a top priority due to budget reductions. This study aims to use the Analytic Hierarchy Process (AHP) method in determining the priority of bridge maintenance in Sekadau Regency based on 4 (four) criteria and 10 (ten sub-criteria) for 3 (three) alternative steel frame bridges, where primary data is obtained based on questionnaires for 3 (three) groups of respondents. The analysis results show that the priority is given to the alternative Balai Sepuak Bridge, located in Balai Sepuak District, with a weight of 0.423. The second priority is the alternative Riam Engkayak Bridge located in Nanga Mahap District, with a weight of 0.416. The third priority is the alternative to the Ayak River Bridge, located in Belitang Hilir District, with a weight of 0.161.